Effects of MgO on dielectric relaxation and phase transition of the ceramic matrix BaBi4Ti4O15 - Gozzo, C.B. (Elsevier, 2019)
BaBi4Ti4O15 (BBT) ceramics doped with magnesium oxide in the weight concentration of 0, 1 and 2% (i.e. BBB_0, BBT_1 and BBT_2, respectively), were prepared by the solidestate reaction method. X-ray diffraction analysis and impedance spectroscopy measurements were employed to study the influence of the structural characteristics on the electrical properties. The formation of the orthorhombic phase for all samples with a decrease in the unit cell volume was due to insertion of Mg2þ into Ti4þ sites. With the increase of magnesium oxide amount there was a decrease in the value of the complex impedance, both real (ZReal), 4.75 107 U to 6.68 106 U, and imaginary (-ZImg), 2.13 107 U to 2.22 106 U, respectively for samples BBT - 0 and BBT - 2. Using an equivalent circuit including the contribution of grain and grainboundaries, it was observed activation energies of 1.169 and 0.874 eV for the grain and 1.320 and 0.981 eV for the grain boundary for samples BBT_0 and BBT_2, respectively. The replacement of Mg2þ into Ti4þ sites shifts the dielectric constant maximum, measured at a fixed frequency, to occur at higher temperatures